The Moderating Role of Loan Monitoring on the Relationship between Macroeconomic Variables and Non-performing Loans in Association of Southeast Asian Nations Countries - Idris, Ismail Tijjani; Nayan, Sabri (International Journal of Economics and Financial Issues, 2016)
The lending banks’ function of loan monitoring plays an important role in sustaining quality loan portfolios and protects risk assets against deterioration thereby keeping Non-Performing Loans (NPLs) within acceptable standards. The aim of this paper is to propose a conceptual model/framework of investigating the moderating role of loan monitoring on the relationship between macroeconomic variables and Non-Performing Loans among ASEAN Economic Community countries. The global problem of NPLs has been persistent and on the rise. Many attempts have been made to investigate the determinant of NPLs yet the problem has remained unexplained. Most of the previous studies have focused on macroeconomic and other environmental variables, industry-specific and bank-specific determinants of NPLs but gave less attention to the moderating role of loan monitoring functions of the lending banks. This paper proposes a framework by adding a moderator of loan monitoring to the existing models of the macroeconmic determinants of NPLs with special attention to the ASEAN Economic Community (AEC) countries that mostly were once heavily confronted with severe banking and financial crises in the late 90s. It is expected that the outcome will assist policymakers in protecting and/or improving the current state of NPLs among AEC member countries. Keywords: Loan monitoring, Macroeconomic variables and Non-Performing Loans JEL Classifications: E01, G21, G32